2020
DOI: 10.11604/pamj.2020.36.64.22987
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and anatomical distribution of diverticular disease in four hospitals in Sudan

Abstract: Introduction: diverticular disease (DD) was thought to be more prevalent in the western countries, especially the white populations, but the recent increase in incidence among African and Asian population, was reported. Up to our knowledge, there is no previous study of DD in Sudan. Methods: this is a descriptive cross-sectional study conducted at the department of endoscopy in four Sudanese hospitals in the period from October 2017 to February 2019. We included all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…[ 12 ] In Sudan, abdominal pain was the main presenting symptom amongst all patients studied—left iliac fossa pain in 58.6% patients, 21.1% in right iliac fossa and generalised abdominal pain in 20.2% and, 57.6% also complained of rectal bleeding. [ 13 ] In this study, rectal bleeding was the commonest sole presentation (60%) or indication for colonoscopy. This was similar to that recorded by Alatise et al .…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…[ 12 ] In Sudan, abdominal pain was the main presenting symptom amongst all patients studied—left iliac fossa pain in 58.6% patients, 21.1% in right iliac fossa and generalised abdominal pain in 20.2% and, 57.6% also complained of rectal bleeding. [ 13 ] In this study, rectal bleeding was the commonest sole presentation (60%) or indication for colonoscopy. This was similar to that recorded by Alatise et al .…”
Section: Discussionmentioning
confidence: 77%
“…Diverticular disease was observed to be common among the elderly in the study population, with an average age of 67 years similar to other African countries and in the USA which also stood at 67. [ 13 ] Though a disease of the elderly, the youngest patient reported in this study was 26 years, while that reported in Zambia was 42 and in Sudan, 17 years. [ 13 14 ] The youngest patient ever documented with colonic diverticulosis was described by Ignacio et al .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This is despite the high prevalence of tuberculosis in this region and the rising incidence of colorectal tumors (14). In Africa, unlike in high-income regions, spontaneous colocutaneous fistulae caused by diverticular disease are expected to be minimal as the incidence of diverticular disease in this population is low (15). Most reported cases of spontaneous colocutaneous fistulae are unilateral and single, with no cases of bilateral or multiple spontaneous fistulae (1,2,7).…”
Section: Discussionmentioning
confidence: 99%